Modeling light response of effective quantum efficiency of photosystem II for C3 and C4 crops - Yang, Xiao-Long; An, Ting; Ye, Zi-Wu-Yin; Kang, Hua-Jing; Robakowski, Piotr; Ye, Zi-Piao; Wang, Fu-Biao; Zhou, Shuang-Xi (Frontiers in Plant Science, 2025)
Effective quantum efficiency of photosystem II (ΦPSII) represents the proportion of photons of incident light that are actually used for photochemical processes, which is a key determinant of crop photosynthetic efficiency and productivity. A robust model that can accurately reproduce the nonlinear light response of ΦPSII (ΦPSII–I) over the I range from zero to high irradiance levels is lacking. In this study, we tested a ΦPSII–I model based on the fundamental properties of light absorption and transfer of energy to the reaction centers via photosynthetic pigment molecules. Using a modeling-observation intercomparison approach, the performance of our model versus three widely used empirical ΦPSII–I models were compared against observations for two C3 crops (peanut and cotton) and two cultivars of a C4 crop (sweet sorghum). The results highlighted the significance of our model in (1) its accurate and simultaneous reproduction of light response of both ΦPSII and the photosynthetic electron transport rate (ETR) over a wide I range from light limited to photoinhibition I levels and (2) accurately returning key parameters defining the light response curves.